The Effectiveness of CBT Group Counseling with Problem Solving and Role Play Techniques to Improve Students’ Emotional Intelligence (Universitas Negeri Semarang, 2020)
This study attempted to analyze the CBT group counseling with problem solving and role play techniques to improve students’ emotional intelligence. The study employed pretest and multiple posttest design. Meanwhile, purposive sampling was used to select 18 experimental subjects assigned to three groups randomly, in other words, there were six students in each group. Their data were collected using emotional intelligence scale. The results of mixed ANOVA test showed that the CBT group counseling with problem solving and role play techniques was effective to improve students’ emotional intelligence by having (F (1.15) = 12.097, p < 0.05). It was also proved by several effects examined, namely time effect (F (2.30) = 1201.32, p < 0.05), and the effect of time and group interaction (F (2.30) = 6. 427, p < 0.05). These asserted that the CBT group counseling with problem solving and role play techniques is effective to improve students’ emotional intelligence.